Quantum simulation experiments with superconducting circuits - Braumüller, Jochen (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2018)
While the universal quantum computer seems not in reach for the near future, this work focusses on analog quantum simulation of intriguing quantum models of light-matter interactions, with the goal of achieving a computational speed-up as compared to classical hardware. Existing building blocks of quantum hardware are used from superconducting circuits, that have proven to be a very suitable experimental platform for the implementation of model Hamiltonians at a high degree of controllability.